Rupture of Rudimentary Horn Pregnancy at 16 Weeks of Gestation - Hanane Houmaid; Abderraouf Hilali (Case Reports in Obstetrics and Gynecology)
Pregnancy in the rudimentary horn is rare and a life-threatening. Rupture of pregnant rudimentary horn in the second trimester is a usual presentation. Early diagnosis and fast management are necessary to decrease the mortality and the morbidity of this pathological entity. This report confirms the diagnostic and therapeutic difficulties of the pregnant rudimentary horn. An emergency laparotomy was taken, and ruptured right rudimentary horn was diagnosed. A hemi-hysterectomy was carried out. The patient’s postoperative follow-up was uneventful, and she left the hospital 5 days after.